Faktor-Faktor yang Mempengaruhi Aksesibilitas UMKM Terhadap Pembiayaan di Bank Syariah (Studi Pada UMKM Kampung Lembur Sawah Mulyaharja) - Aziz, Imam Abdul; Junaidi; Brawijaya, Andri (FEBI UIN Sunan Kalijaga, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a very strategic role in developing the region , and can support large industries and become one of the drivers of a country's progress. However, in its operations, MSMEs have many obstacles, one of which is capital from Islamic banks in the form of financing. This study aims to determine the factors that affect the accessibility of SMEs to financing in Islamic banks. The method used in this study is a quantitative method with the help of SPSS For Windows Version 23 data processing software. The population in this study is the MSMEs of village Lembur Sawah Mulyaharja, totaling 86 SMEs with a total sample of 86 SMEs. The results showed that the information, guarantee and location factors had a significant and positive effect both simultaneously and partially on the accessibility of MSMEs in Islamic banks. The most dominant factor influencing the accessibility of MSMEs to Islamic bank financing is the information factor. The information needed for MSMEs in accessing financing at Islamic banks is information related to procedures, financing requirements, system convenience, profit sharing, and financing retrieval services at the concerned Islamic bank.